ACT‐ONE ‐ ACTION at last on cancer cachexia by adapting a novel action beta‐blocker. Issue 4 (5th August 2016) - Lainscak, Mitja; Laviano, Alessandro
Abstract: Novel action beta‐blockers combine many different pharmacological effects. The espindolol exhibits effects through β and central 5‐HT1α receptors to demonstrate pro‐anabolic, anti‐catabolic, and appetite‐stimulating actions. In the ACT‐ONE trial, espindolol reversed weight loss and improved handgrip strength in patients with cachexia due to non‐small cell lung cancer or colorectal cancer. With this trial, another frontier of cachexia management is in sight. Nonetheless, more efficacy and safety data is needed before new therapeutic indications for novel action beta‐blockers can be endorsed.